Museums in a Digital Culture - van den Akker, Chiel; Legêne, Susan (Amsterdam University Press, 2017)
The experience of engaging with art and history has been utterly transformed by information and communications technology in recent decades. We now have virtual, mediated access to countless heritage collections and assemblages of artworks, which we intuitively browse and navigate in a way that wasn't possible until very recently. This collection of essays takes up the question of the cultural meaning of the information and communications technology that makes these new engagements possible, asking questions like: How should we theorise the sensory experience of art and heritage? What does information technology mean for the authority and ownership of heritage?